Relevansi Konsep Penciptaan Alam Semesta Lontar Bhuwana Sangksepa dan Pemahaman Kosmos Masyarakat Bali - Ida Bagus Wika Krishna; Krisna S. Yogiswari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Local wisdom is a local idea or view that is wise, full of wisdom, is of a good nature which is embedded and followed by members of the community. This view is closely related to the nature of traditional institutions, strict contextuality as well as universal. Lontar Bhuwana Sangksepa as a form of traditional literature that contains a lot of local wisdom, especially about the process of creating the universe. This study uses a qualitative approach with the hermeneutic method. This study found that the cosmological values contained in Lontar Bhuwana have an influence on the daily life of the Balinese people, this can be seen from the determination of space in the Balinese residential pattern and the calculation of the implementation and form of ritual facilities performed by the Balinese people are strongly influenced by the understanding of the cosmos. developing in society. This study also finds that there is a relevance of the concept of cosmology in Lontar Bhuwana Sangksepa to the understanding of the Balinese cosmos.Keywords: Cosmology, Balinese Society, Lontar Bhuwana Sangksepa